2023
DOI: 10.3892/mmr.2023.13064
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ANLN inhibits the progression of lung adenocarcinoma via pyroptosis activation

Abstract: Significant advancements have been achieved in the area of molecular targeted therapy for lung adenocarcinoma (LUAD). However, the complex molecular patterns and high heterogeneity of LUAD confine the efficacy of these therapies to a specific subset of patients; therefore, it is necessary to explore novel targets for LUAD treatment. The expression levels of anillin (ANLN) in LUAD were analyzed using the Gene Expression Profiling Interactive Analysis database. Furthermore, the association between ANLN gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…This is in concordance with a positive correlation between the expression of KIF18A and ANLN. Furthermore, numerous studies have reported the overexpression of ANLN as a potential biomarker of lung cancer progression [ 67 , 68 ]. The elevated expression of CCNE2 is also significantly correlated with advanced tumors and worse OS in lung cancer [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in concordance with a positive correlation between the expression of KIF18A and ANLN. Furthermore, numerous studies have reported the overexpression of ANLN as a potential biomarker of lung cancer progression [ 67 , 68 ]. The elevated expression of CCNE2 is also significantly correlated with advanced tumors and worse OS in lung cancer [ 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed the involvement of ANLN in the initiation and progression of various cancer types. For example, in lung cancer, the knockdown of ANLN can activate pyroptosis and inhibit the progression of lung adenocarcinoma [32]. Similarly, elevated ANLN expression in liver tumors is linked to poor prognosis, and ANLN knockdown has been demonstrated to inhibit the occurrence and progression of liver tumors by influencing cytokinesis impairment.…”
Section: Discussionmentioning
confidence: 99%